New synthetic pathway leading to oxospirochlorins. Issue 38 (12th June 2018) - Śniechowska, Justyna; Paluch, Piotr; Pawlak, Tomasz; Bujacz, Grzegorz D.; Danikiewicz, Witold; Potrzebowski, Marek J.
Abstract : Oxospirochlorins – novel analogs of porphyrinoids were synthesized and characterized by various methods including X-ray, NMR spectroscopy and mass spectrometry. Abstract : In this work we propose a completely new approach for the synthesis of spirochlorin derivatives based on the use of an imino-keto intermediate formed in situ from 2-amino-5, 10, 15, 20-tetraphenylporphyrins and inverse electron demand Diels–Alder (iEDDA) cycloaddition with 3, 6-di-2-pyridyl-1, 2, 4, 5-tetrazine. The mechanism of reaction was analyzed employing theoretical methods by comparing the difference in energy of Frontier Molecular Orbitals (FMO) for appropriate reagents. Ground-state molecular electrostatic (ESP) potential maps were employed as additional tools allowing explanation of the reactivity of substrates. The new class of spirochlorin compounds was fully characterized by means of mass spectrometry, IR, liquid and solid state NMR and X-ray crystallography. Correlation between molecular structure and optical properties for the obtained title compounds is discussed.